Isbat Nikah dalam Legalitas Hukum Islam dan Perdata di Indonesia Perspektif Maslahah Mursalah - Aziz, Abdul; Maksum, Ghufron; Nugraha, Iqbal Subhan (Tasyri' : Journal of Islamic Law, 2024)
Marriage validation is a crucial legal mechanism in Indonesia, especially for marriages that are not officially registered. This study explores marriage validation from the perspective of Maslahah mursalah, a principle in Islamic law emphasizing public interest and welfare. Maslahah mursalah serves to bridge legal gaps when the texts of Sharia law do not explicitly address specific situations, such as marriages that are religiously valid but unregistered. Within the framework of Indonesian civil law, marriage validation, which involves submitting a petition to the religious court, enables the formal recognition of marriages to ensure the protection of family rights, such as inheritance and alimony. The application of maslahah mursalah in marriage validation contributes to social justice by providing decisions that consider practical community needs and contemporary conditions. This research demonstrates how this principle can be integrated into positive law to address new challenges in family law enforcement, ensuring that legal decisions align with principles of justice and public welfare. Thus, marriage validation from the perspective of maslahah mursalah acts as a bridge between Sharia law and the realities of civil law in Indonesia.